Using electricity tariffs and thermal comfort management to promote residential energy decarbonization - Andrea Vecchi; Michael John Brear (iScience)
Summary: Household thermal demand supply through electricity could reduce emissions, but also compromise the operation of electricity distribution networks. In this work, suitable electricity tariff designs and household thermal management are investigated, individually and in combination, as ways to enhance network operability, support electrification, and improve system-level performance. Optimization results from eight combinations of building type, vintage, and climates in Australia show considerable social benefits resulting from the measures explored. Electricity tariffs that include a demand charge contain peak loads without increasing household costs. Furthermore, emission and cost savings from looser thermostat setpoints and building pre-heating/cooling are demonstrated. These are also found to reduce the upfront investment in household electrification to levels comparable with current, dual-fuel (electricity and natural gas) practices. Subject to the degree of occupants’ acceptance and policy adoption, a significant potential to mitigate, and even avoid, anticipated network strain, while tackling pressing affordability and decarbonization challenges is demonstrated.